CHF5074 Reduces Biomarkers of Neuroinflammation in Patients with Mild Cognitive Impairment: A 12-Week, Double-Blind, Placebo- Controlled Study - Ross, Joel; Sharma, Sanjiv; Winston, Jaron; Nunez, Margarita; Bottini, Gabriella; Franceschi, Massimo; Scarpini, Elio; Frigerio, Enrico; Fiorentini, Francesco; Fernandez, Mercedes; Sivilia, Sandra; Giardino, Luciana; et al. (Current Alzheimer Research, 2013)
As neuroinflammation is an early event in the pathogenesis of Alzheimer’s disease, new selective antiinflammatory drugs could lead to promising preventive strategies. We evaluated the safety, tolerability, pharmacokinetics and pharmacodynamics of CHF5074, a new microglial modulator, in a 12-week, double-blind, placebo-controlled, parallel groups, ascending dose study involving 96 MCI patients. Subjects were allocated into three successive study cohorts to receive ascending, titrated doses of CHF5074 (200, 400 or 600 mg/day) or placebo. Vital signs, cardiac safety, neuropsychological performance and safety clinical laboratory parameters were assessed on all subjects. Plasma samples were collected throughout the study for measuring drug concentrations, soluble CD40 ligand (sCD40L) and TNF-α. At the end of treatment, cerebrospinal fluid (CSF) samples were optionally collected after the last dose to measure drug levels, β- amyloid1-42 (Aβ42), tau, phospho-tau181, sCD40L and TNF-α. Ten patients did not complete the study: one in the placebo group (consent withdrawn), two in the 200-mg/day treatment group (consent withdrawn and unable to comply) and seven in the 400-mg/day treatment group (five AEs, one consent withdrawn and one unable to comply). The most frequent treatment-emergent adverse events were diarrhea, dizziness and back pain. There were no clinically significant treatmentrelated clinical laboratory, vital sign or ECG abnormalities. CHF5074 total body clearance depended by gender, age and glomerular filtration rate. CHF5074 CSF concentrations increased in a dose-dependent manner. At the end of treatment, mean sCD40L and TNF-α levels in CSF were found to be inversely related to the CHF5074 dose (p=0.037 and p=0.001, respectively). Plasma levels of sCD40L in the 600-mg/day group were significantly lower than those measured in the placebo group (p=0.010). No significant differences between treatment groups were found in neuropsychological tests but a positive dose-response trend was found on executive function in APOE4 carriers. This study shows that CHF5074 is well tolerated in MCI patients after a 12-week titrated treatment up to 600 mg/day and dose-dependently affects central nervous system biomarkers of neuroinflammation.
Keywords: neuroinflammation